1991
DOI: 10.1021/ac00014a024
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry of peptides using hybrid and four-sector instruments: A comparative study

Abstract: Product-ion spectra produced by high- and low-energy collisionally activated dissociation (CAD) of [M + H]+ ions of a series of peptides (Mr 550-2500) have been compared on four-sector and hybrid tandem mass spectrometers, respectively. The fast atom bombardment product-ion spectra obtained for the smallest peptide analyzed (methionine-enkephalin) were remarkably similar, but substantial differences in fragmentation were observed for the heavier analytes. For peptides with Mr greater than 1000, more complete s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 75 publications
7
40
0
Order By: Relevance
“…Since that time, improvements in sequencing have been spurred by the development of protein-identification algorithms as well as a better understanding of peptide dissociation in the gas phase. The latter advancement has been achieved by exploring the effects of peptide size, sequence, gasphase basicity, charge state, and secondary structure on fragmentation [62][63][64][65][66][67][68][69][70]. Surface-induced dissociation was influential in helping to develop a general framework for peptide fragmentation through the energyresolved study of systematically varied model peptides.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, improvements in sequencing have been spurred by the development of protein-identification algorithms as well as a better understanding of peptide dissociation in the gas phase. The latter advancement has been achieved by exploring the effects of peptide size, sequence, gasphase basicity, charge state, and secondary structure on fragmentation [62][63][64][65][66][67][68][69][70]. Surface-induced dissociation was influential in helping to develop a general framework for peptide fragmentation through the energyresolved study of systematically varied model peptides.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
“…As the number of tandem MS peptide studies increased, several researchers began to notice enhanced fragmentation at particular amino acid residues that prevented complete backbone cleavage, and resulted in incomplete sequencing information [59,62,64,68,70,[75][76][77][78]. Protein-identification algorithms may benefit from the incorporation of selective cleavage rules if residuespecific influences are more completely understood.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
“…This process is known to be less favoured. 19 For compounds 2 to 7, fission of the DP amide bond is one of the most abundant processes compared to other amide bond cleavages in these peptides. The facile cleavage of the DP bond does not seem to depend on the length of the peptide chain.…”
Section: Resultsmentioning
confidence: 99%
“…26 Although it has been reported that the energy of fragmentation in low-energy CID might be insufficient to break the bond between the a-carbon and the carbonyl, 57 x-ions are included in the C-terminal ion series of the theoretical MS/MS. Also included in the peaks of this spectra are what are known as internal fragment ions 56,[59][60][61] …”
Section: Scoring Candidate Sequencesmentioning
confidence: 99%